SARS-CoV-2 contamination potential in environmental and wastewaters in the Algarve region, Southern Portugal - Galvão, Helena M.; Mendes, Pedro J.; Figueiredo, Aida; Santos, Ricardo; Monteiro, Silvia (Frontiers in Water, 2022)
The Ria Formosa, Southern Portugal (Algarve) is a mesotidal lagoon with restricted exchange with Atlantic Ocean. Due to arid Mediterranean climate and absence of large freshwater inputs, the lagoon remains hypersaline relative to adjacent ocean (≥37 psu). Generally, fecal coliforms and land-derived bacteria do not survive long in seawater due to UV, osmotic shock, oligotrophy and competition with marine bacteria. However, survival of human pathogenic viruses in natural waters remains relatively unknown. In view of 2020–2021 SARS-CoV-2 pandemic, this preliminary study aimed to estimate potential contamination by wastewater and persistence in marine environment. Five sampling campaigns (45 total samples) were completed in 2020 and 2021 at three stations in the lagoon, as well as inflow and outflow from three wastewater treatment plants (WWTPs). Despite relatively high fecal contamination at lagoon stations, SARS-CoV-2 could not be detected in surface waters using improved methodology. Untreated wastewaters were positive at Faro-Aeroporto 21/10/2020, 14/12/2020, 08/03/2021; Vilamoura 21/10/2020, 14/12/2020; Olhão 14/12/2020. All treated wastewaters were negative, as well as environmental samples. Highest viral titers were observed in Faro-Aeroporto WWTP on 8 March 2021 (1.35 x 105 genomic copies L−1) coinciding with peak SARS-CoV-2 cumulative positive cases in Algarve (2.03 x 104), yet SARS-CoV-2 was not detected in Vilamoura and Olhão raw wastewater then. Thus, the contamination potential of SARS-CoV-2 seemed non-existent in the Ria Formosa during peak pandemic surges in Algarve. However, predicted climate change and its impact on microbial populations remains a challenge to be addressed by both health and tourist authorities.